Sabʿ rasāʾil - Dawānī, Jalāl al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
The history of Islamic philosophy was shaped by many great thinkers over a long period of time. As is well known, the Persianate world played an important role in this, almost from the very beginning. In the fifteenth and sixteenth centuries, the city of Shiraz saw the rise of a number of thinkers who together came to represent the 'School of Shiraz' in philosophy. A major figure in this school was Jalāl al-Dīn Dawānī (d. 908/1502-03). A specialist in theology and philosophy, Dawānī's fame reached much beyond the confines of Shiraz, from the Ottoman empire all the way to the Indian subcontinent. Dawānī's religious proclivities have been subject of debate, the question being if he ever really was a Sunnī. It is therefore not without significance that the present volume should contain two works by him on Sunnī philosophical theology as well as three other texts of unmistakeably Shīʿī signature.